A fed-batch fermentation process for poly (3-hydroxybutyrate-co-3-hydroxyvalerate) production by Yangia sp. ND199 using molasses as substrate - Thuoc, Doan Van; Phong, Tran Huu; Khuong, Dang Minh (Academia Journal of Biology, 2015)
A locally isolated halophilic bacterium, Yangia sp. ND199 was able to use molasses as substrate for copolymers poly(3-hydroxybutyrate-co-3-hydroxyvalerate) [P(3HB-co-3HV)] production. Cell dry weight (CDW) of 6.37 g/l, P(3HB-co-3HV) content of 43.1 wt% and P(3HB-co-3HV) concentration of 2.75 g/l were obtained by Yangia sp. after 60 h of cultivation in flask. In a batch cultivation mode in a fermentor, the CDW was increased to 9.1 g/l but P(3HB-co-3HV) content was decreased to 37 wt%. Fed-batch fermentation with two different nutrient feeding strategies was used. High CDW of 54.8 g/l was obtained after 54 h of cultivation but P(3HB-co-3HV) content was still low (39.8 wt%). Two-step fed-batch fermentation with two different nutrient feeding strategies was then designed. High CDW of 50 g/l and P(3HB-co-3HV) content of 52.9 wt% were obtained after 54 h of cultivation. The two-step fed-batch process designed here for the production of P(3HB-co-3HV) by Yangia sp. ND199 can be developed and used for further studies.